Two-wheeled Sensibility: Sensory Engagement with Place in British, American and French Cycling Narratives, 1880–1914 - Una Brogan (Cahiers Victoriens et Edouardiens, 2016)
Texts written in the early days of cycling hint at the appearance of a new and paradoxical engagement with space. On the one hand, the bicycle was a technology which provided personal mobility to a wide section of the population, whilst encouraging a multisensory engagement with landscape in the wake of the railways. On the other hand, cyclists’ accounts bear testament to a certain mechanization of the body and the senses, contributing to a visual, distancing experience of place which the railways had inaugurated. I argue that it is the unique combination of these two registers that defines the turn-of-the-century cycling aesthetic.